LT

tìm \(x_1;x_2;x_3;......;x_{2011}\) biet 

\(\frac{x_1-1}{2010}=\frac{x_2-2}{2009}=.....=\frac{x_{2010}-2010}{1}\)va \(x_1+x_2+.....+x_{2011}=2\left(1+2+3+...+2010\right)\)

 

 

DH
22 tháng 2 2017 lúc 11:55

\(\frac{x_1-1}{2010}=\frac{x_2-2}{2009}=...=\frac{x_{2010}-2010}{1}=\frac{\left(x_1-1\right)+\left(x_2-2\right)+...+\left(x_{2010}-2010\right)}{1+2+...+2010}\) (TC DTSBN)

\(=\frac{\left(x_1+x_2+...+x_{2010}\right)-\left(1+2+...+2010\right)}{1+2+...+2010}=\frac{2.\left(1+2+...+2010\right)-\left(1+2+...+2010\right)}{1+2+...+2010}=1\)

\(\Rightarrow x_1-1=2010;x_2-1=2009;....;x_{2010}-2010=1\)

=> x1 = x2 = x3 =..... = x2010 = 2011

Bình luận (0)